The wedding planner. - Steel, Danielle (Delacorte Press, 2023)
Faith Ferguson is New York's most in-demand wedding planner, an arbiter of taste for elegant affairs, lavish ceremonies, and exclusive fAetes. She appreciates a simple celebration as much as a dazzling event, for she knows that a dream wedding is not necessarily the most expensive one. As much as Faith enjoys her work, her two failed engagements leave her with no desire to get married herself. She finds fulfillment in her close relationship with her twin sister, Hope, her role as a mentor for her assistant, Violet, and her career. This year, new clients have flocked to her, and she signs up an extravagant reception, a mid-sized gathering, and an intimate soiraee, in addition to her mother's next marriage and Violet's modest ceremony. Faith finds herselfforming bonds with her new clients and their loved ones--most notably the handsome brother of one of her grooms. But weddings are not always all champagne and roses, and in no time, Faith is grappling with private quarrels, unplanned pregnancies, family scandals, dark secrets, and the possibility of cancelled ceremonies. Through her own journey, Faith will prove once and for all that there is not just one path to happily ever after